Israel's prophets and Israel's past: essays on the relationship of prophetic texts and Israelite history in honor of John H. Hayes - Kelle, Brad E.; Hayes, John Haralson; Moore, Megan Bishop (Library of Hebrew bible/Old Testament studies, 2006)
Introduction / Brad E. Kelle and Megan Bishop Moore -- The prophets in historical perspective. Israel's past : our "best guess scenario" / J. Maxwell Miller ; Writing Israel's history using the prophetic books / Megan Bishop Moore ; De-historicizing and historicizing tendencies in the twelve prophetic books : a case study of the heuristic value of a historically anchored systemic approach to the corpus of prophetic literature / Ehud Ben Zvi ; Ancient Israelite prophets and Greek political orators : analogies for the prophets and their implications for historical reconstruction / Brad E. Kelle -- The prophets in historical context. Amos the prophet and Amos the book : historical framework / Gene M. Tucker ; Redaction, history, and redaction-history of Amos in recent scholarship / Marc Zvi Brettler ; Amos, man and book / Philip R. Davies ; "How can Jacob stand? he is so small!" (Amos 7:2) : the prophetic word and the re-imagining of Israel / J. Gordon McConville ; The biblical [QRZM] : what is it? / Oded Borowski ; Relating prophets and history : an example from Hosea 13 / Stuart A. Irvine ; A prostitute unlike women : whoring as metaphoric vehicle for foreign alliances / Peggy L. Day ; (E)Masculinity in Hosea's political rhetoric / Susan E. Haddox ; Isaiah's Egyptian and Nubian oracles / J.J.M. Roberts ; Herodotus' Histories 2.141 and the deliverance of Jerusalem : on parallels, sources, and histories of ancient israel / Brent A. Strawn ; The royal oracle in Ezekiel 37:15-28 : Ezekiel's reflection on Josiah's reform / Marvin A. Sweeney ; Necessary enemies : Nebuchadnezzar, YHWH, and Gog in Ezekiel 38-39 / Julie Galambush ; Zerubbabel, Zechariah 3-4, and post-exilic history / Bob Becking ; Ezekiel spinning the wheels of history / Alice W. Hunt -- The prophets in historical tradition and reception. Rhyme and reason : the historical résumé in Israelite and early Jewish thought / Carol A. Newsom ; The ambiguous role of Moses as prophet / David L. Petersen ; The place of Israelite prophecy in human history / Martin J. Buss